Expression of VCAM in Male Wistar Rats (Rattus norvegicus) with Hypercholesterolemia Supplemented with Pumpkin Seeds (Cucurbita moschata Duch) Extract - Proboningsih, Jujuk; Wirjatmadi, Bambang; Kuntoro, Kuntoro; Adriani, Merryana (Health Notions, 2018)
Treatment of cardiovascular diseases tends to be expensive and requires long-term therapy. Investigation about the effect of pumpkin seeds on prevention of endothelial dysfunction of blood vessel has never been reported yet, accordingly, bodies of research are required to know its effectiveness. This study aimed to analyze the expression of Vascular Cell Adhesion Molecule (VCAM) in male Wistar rats (Rattus norvegicus) with hypercholesterolemia supplemented with pumpkin seeds extract (Cucurbita moschata Duch). This was an experimental laboratory study with randomized post-test control group design. The independent variable was pumpkin seeds extract, and the dependent one was expression of VCAM. Data analysis employed chi-square test to test the difference between control and treatment groups. Study results showed that there was significant difference (p=0.000) between VCAM expression in group-K2 (positive control) as compared to group-K1 (negative control) and group-K5 (treatment group-dose 3) Î±=0.001, whereas no significant difference was found between that of as compared to group-K3 (treatment group-dose 1) Î±=0.125 and group-K4 (treatment group-dose 2) Î±=0.05. The study showed reduction of VCAM expression in treatment groups consisted of male Wistar rats with hypercholesterolemia supplemented with pumpkin seeds (Cucurbita moschata Duch) extract. Keywords: Pumpkin seeds, VCAM expression, hypercholesterolemia